PERCY JACKSON’S JOURNEY TO FIND HIS IDENTITY - Dian Natalia; Jenny M. Djundjung (Institute of Research and Community Outreach - Petra Christian University, 2015)
Percy Jackson: The Lightning Thief and Percy Jackson: Sea of Monsters are two films that are taken from Rick Riordan’s famous Percy Jackson Series. Percy Jackson series is talking about a sixteen-year-old boy who does not know that he is a demigod and faces problem as a human being. Because he does not know that he is a demigod and faces problem as a human being, he conduct a journey to search his identity. In his journey to search his identity, Percy who has a certain disability as a teenager, can become a hero and save the gods’ world. In this paper, I will reveal the way Percy Jackson finds his identity by taking a journey and makes him become a hero in the world of the gods. I will combine the theory of Joseph Campbell, the hero’s journey, and the theory of Erik Erikson, the identity crisis, to analyze Percy Jackson’s journey to search for his identity. Besides Percy finds his identity in the journey, he also finds himself as a hero